Protective Effect of Cyanidin-3-O-Glucoside against Ultraviolet B Radiation-Induced Cell Damage in Human HaCaT Keratinocytes - Hu, Yunfeng; Ma, Yuetang; Wu, Shi; Chen, Tianfeng; He, Yong; Sun, Jianxia; Jiao, Rui; Jiang, Xinwei; Huang, Yadong; Deng, Liehua; Bai, Weibin (Frontiers in Pharmacology, 2016)
Ultraviolet radiation is the major environmental harmful factor that has emotional impact on human skin. The aim of the present study was to determine the mechanism of protection of cyanidin-3-O-glucoside against ultraviolet B (UVB) -induced damage to human HaCaT keratinocytes. Our results show that cyanidin-3-O-glucoside decreased the levels of intracellular reactive oxygen species generated by UVB treatment. cyanidin-3-O-glucoside also decreased the UVB-augmented levels of the DNA damage indicators phospho-p53 and phospho-ATM/ATR. In addition, cyanidin-3-O-glucoside protected keratinocytes from UVB-induced injury by overturning the disruption of mitochondrial membrane potential and reversing apoptosis. The expression of anti-apoptotic protein B-cell lymphoma 2 (Bcl-2) was attenuated in UVB-exposed cells but restored in UVB/cyanidin-3-O-glucoside-treated cells. Furthermore, expression of the proapoptotic proteins Bcl-2-associated X (Bax) and the key apoptosis executer cleaved caspase-3 were increased in UVB-irradiated cells and decreased in UVB/cyanidin-3-O-glucoside-treated cells. For these reasons, the results demonstrate that cyanidin-3-O-glucoside protects human keratinocytes against UVB-induced oxidative stress and apoptosis. Our study provides a theoretical basis for the use of cyanidin-3-O-glucoside in the fight against light damage .